Effects of correcting metabolic acidosis on muscle mass and functionality in chronic kidney disease: a systematic review and meta‐analysis - Wesley J. Visser; Elma E.M. van deBraak; Anneke M.E. deMik ‐ van Egmond; Anna C. van derBurgh; Nicole M. deRoos; Inez Jans; Iris van derHoef; Joanne F. Olieman; Ewout J. Hoorn; David Severs (Wiley, 2023)
Abstract Metabolic acidosis unfavourably influences the nutritional status of patients with non‐dialysis dependent chronic kidney disease (CKD) including the loss of muscle mass and functionality, but the benefits of correction are uncertain. We investigated the effects of correcting metabolic acidosis on nutritional status in patients with CKD in a systematic review and meta‐analysis. A search was conducted in MEDLINE and the Cochrane Library from inception to June 2023. Study selection, bias assessment, and data extraction were independently performed by two reviewers. The Cochrane risk of bias tool was used to assess the quality of individual studies. We applied random effects meta‐analysis to obtain pooled standardized mean difference (SMD) and 95% confidence intervals (CIs). We retrieved data from 12 intervention studies including 1995 patients, with a mean age of 63.7 ± 11.7 years, a mean estimated glomerular filtration rate of 29.8 ± 8.8 mL/min per 1.73 m2, and 58% were male. Eleven studies performed an intervention with oral sodium bicarbonate compared with either placebo or with standard care and one study compared veverimer, an oral HCl‐binding polymer, with placebo. The mean change in serum bicarbonate was +3.6 mEq/L in the intervention group and +0.4 mEq/L in the control group. Correcting metabolic acidosis significantly improved muscle mass assessed by mid‐arm muscle circumference (SMD 0.35 [95% CI 0.16 to 0.54], P < 0.001) and functionality assessed with the sit‐to‐stand test (SMD −0.31 [95% CI −0.52 to 0.11], P = 0.003). We found no statistically significant effects on dietary protein intake, handgrip strength, serum albumin and prealbumin concentrations, and blood urea nitrogen. Correcting metabolic acidosis in patients with CKD improves muscle mass and physical function. Correction of metabolic acidosis should be considered as part of the nutritional care for patients with CKD.